2020
DOI: 10.1007/s10924-020-01736-5
|View full text |Cite
|
Sign up to set email alerts
|

Starch-Leather Waste Gelatin Films Cross-Linked with Glutaraldehyde

Abstract: Gelatin extracted from chromium-tanned leather wastes (CTLW) has a lower molar mass because of the more aggressive extraction process needed to disrupt chromium-collagen bonds when compared to gelatin extracted from the bones, skin, and connective tissues of animals. As a consequence, CTLW gelatin is more hydrophilic, thus it is harder to apply in the production of polymers. To overcome this issue, in this study, films produced with starch, CTLW gelatin, commercial gelatin (as a comparative), and their blends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Jin et al noticed that EAB (%) of jackfruit filum polysaccharide film increased after the addition of TiO 2 NPs. Scopel et al also reported that the CH/starch/glycerol films had the highest value of EAB (60.11%) when comparing with films used as mulches in agriculture.…”
Section: Resultsmentioning
confidence: 94%
“…Jin et al noticed that EAB (%) of jackfruit filum polysaccharide film increased after the addition of TiO 2 NPs. Scopel et al also reported that the CH/starch/glycerol films had the highest value of EAB (60.11%) when comparing with films used as mulches in agriculture.…”
Section: Resultsmentioning
confidence: 94%
“…Comparing the films produced with CTLW and COM gelatin (control), it can be noted that the CTLW films show higher interaction with water, characterized by higher water vapor permeability and solubility in water. This is can be attributed to the hydrolysis of the gelatin molecules during the extraction process, which renders them more hydrophilic and reduces their molecular mass 9 . There are also hygroscopic salts present, enhancing water interaction properties 10 …”
Section: Resultsmentioning
confidence: 99%
“…For example, the extraction of gelatin for the application in biodegradable films is a sustainable alternative. Its application in cosmetics or food is not indicated because it is a waste containing chromium 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their use is becoming more and more restrictive, due to their potential risk to human health and environmental issues, especially when Cr(III) is oxidized to Cr(VI), which is a human carcinogen. [10][11][12] Therefore, the development of an ecofriendly chrome-free metal, tanning agent is of paramount importance for the sustainable development of the leather science and industry. In addition, because of the high coordination ability of metals as the tanning agents, the metal species can strongly react with the collagen fibers in the initial stage of the tanning process, leading to a metal overload on the leather surface, which results in a non-uniform penetration and a consequently weak tanning effect.…”
mentioning
confidence: 99%